2016
DOI: 10.1021/acsami.6b04494
|View full text |Cite
|
Sign up to set email alerts
|

Outstanding Antibiofilm Features of Quanta-CuO Film on Glass Surface

Abstract: Intelligently designed surface nanoarchitecture provides defined control over the behavior of cells and biomolecules at the solid-liquid interface. In this study, CuO quantum dots (quanta-CuO; ∼3-5 nm) were synthesized by a simple, low-temperature solution process and further formulated as paint to construct quanta-CuO thin film on glass. Surface morphological characterizations of the as-coated glass surface reveal a uniform film thickness (∼120 ± 10 nm) with homogeneous distribution of quanta-CuO. The antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Especially for glucose sensing, ZnO nanostructures are universal choice of researchers because of their simple and easy synthesis at low temperature in different morphology with high crystallinity, good optical properties, excellent electrical characterstics 20, 21 . In our previous studies, we have shown that vertically-grown ZnO nanostructures on electrode surface have immense capability to hold enzymes because of their nanostructure morphology and high surface area, thereby enhancing overall sensing performance of the enzymatic sensors 2224 .…”
Section: Introductionmentioning
confidence: 99%
“…Especially for glucose sensing, ZnO nanostructures are universal choice of researchers because of their simple and easy synthesis at low temperature in different morphology with high crystallinity, good optical properties, excellent electrical characterstics 20, 21 . In our previous studies, we have shown that vertically-grown ZnO nanostructures on electrode surface have immense capability to hold enzymes because of their nanostructure morphology and high surface area, thereby enhancing overall sensing performance of the enzymatic sensors 2224 .…”
Section: Introductionmentioning
confidence: 99%
“…have shown great potential for different sensing devices fabrication202122232425. Among them, nanostructured ZnO with band gap of 3.37 eV is an excellent candidate to be used as matrix for biosensor fabrication due to its simple and cost-effective synthesis, high surface area, low toxicity, good chemical stability and biological compatibility, and high electron mobility262728. Importantly, high isoelectric point (IEP = ~9.5) of ZnO makes it suitable for absorption of low IEPs proteins or enzymes such as uricase (IEP = ~4.64) at physiological pH, because the enzyme immobilization is primarily driven by electrostatic interaction29.…”
mentioning
confidence: 99%
“…Zinc oxide (ZnO) nanostructures have strong sensing performance toward the bio-analyte that makes them an excellent candidate to be employed as active sites in electrochemical biosensors ( Li et al, 2014 ). ZnO nanostructures are easily synthesized at low temperatures and demonstrate various morphologies with excellent electrical characteristics, high crystallinity, and strong optical properties ( Tripathy et al, 2012 ; Tripathy et al, 2016 ). Moreover, ZnO nanostructures offer a wide surface area for modifying nanostructures to obtain valuable NEG sensor devices ( Ahmad et al, 2017a ; Ahmad et al, 2017b ).…”
Section: Electrochemical Detection Of Glucose On Co Ni Zn Cu Fe Mn Ti Ir Rh Pt Pd Au Based Negsmentioning
confidence: 99%